Development of The Momentum Material E-Module Assisted with Tracker Software to Improve Students' Understanding of Concepts - Dina Aulia, Egi; Subali, Bambang (Universitas Tidar, 2022)
Efforts to increase understanding concepts in the learning process can be done in various ways, one of which is the use of teaching materials in the form of learning modules. This research focuses on the development of momentum material e-modules assisted by Software Tracker. Software Tracker has the ability to track the motion of an object, so various information needed for analysis of a motion event can be obtained. The use of e-modules aims to improve students' conceptual understanding of the momentum material. The method used in this research is Research and Development with the ADDIE development model. The preliminary stage aims to analyze the needs of learning media. After that, the preparation of momentum material e-modules was then developed with additional video analysis activities assisted by a software tracker. Lastly is implementation, where e-modules are piloted on a small and large scale. After the implementation stage, it is known the effect of using the e-module on momentum material. Based on the analysis data, the use of e-modules assisted by a software tracker can improve students' conceptual understanding of the momentum material with an N-Gain score of 0,63 which is included in the medium category.